Comparison of perventricular and percutaneous ultrasound-guided device closure of perimembranous ventricular septal defects - Huang, Liu Liu; Chen, Mai; Zeng, De Cai; Su, Chun Xiao; Jiang, Chun Lan; Zheng, Bao Shi; Wu, Ji; Li, Shi Kang (Frontiers in Cardiovascular Medicine, 2023)
Background Ultrasound-guided percutaneous device closure of perimembranous ventricular septal defects (PmVSD) is a minimally invasive recent treatment approach. Perventricular PmVSD device closure is an emerging radiation-free intervention, yet it comes with certain limitations. No studies compared both of these treatment approaches. Methods We performed a retrospective institutional data comparison of percutaneous (PCP Group, n = 138) and perventricular (PVP Group, n = 67) ultrasound-guided device closure procedures in 205 patients with PmVSD between March 2017 and December 2022. Results Patients of the PCP and PVP groups had a median age of 4.9 years (IQR, 3.1–14.0) and 5.3 years (IQR, 3.4–13.1) respectively. The median PmVSD diameter in the PCP Group was 4.0 mm (IQR, 3.3–5.3) and 5.2 mm (IQR, 4.0–7.0) in the PVP Group (p = 0.001). There was no significant difference in success rates between the PCP and PVP Groups (intention-to-treat population, 88.4% vs. 92.5%, p = 0.36; as-treated population, 88.4% vs. 89.3%, p = 0.84). 5/8 failed percutaneous cases that were shifted to the perventricular approach were successful. Compared to the PVP Group, patients of the PCP group experienced a significant decrease in ventilation time, drainage volume, and postoperative hospital stay (p < 0.001). The median follow-up period was 24 months (IQR, 6–42) for the PCP group and 61 months (IQR, 53–65) for the PVP group. The overall severe adverse event rate was 0% in the PCP group and 3.0% in the PVP group. Conclusions Perventricular and percutaneous ultrasound-guided device closure of PmVSD are both effective and safe treatment options. The percutaneous approach offers less trauma and faster recovery and may be the preferred approach in selected patients.